Recuperação de áreas degradas no semiárido com tamboril usando diferentes técnicas de manejo - Pontes Filho, Roberto Albuquerque (2016)
The hydrogels (compounds of polyacrylamide - PA) and carnauba straw have been indicated for use in agriculture as soil conditioners, for hydrogels can absorb large amounts of water, increasing the retention of this the ground, and carnauba straw coverage reduces the loss of stored water. As a result, both have their use proposed for the revegetation of degraded areas. So if hypothesized that the use of hydrogel associated with carnauba straw benefits the establishment of tamboril [Enterolobium contortisilliquum (Vell.) Morong] and improves the quality of degraded soils in the semiarid region. At that aimed to determine the most appropriate dose of hydrogel for the establishment of tamboril in two different environments; the efficiency of hydrogel-dose association with and without the addition of carnauba straw and effects of the combination hydrogel-bagana on soil structure and soil organic carbon fraction. Therefore, two experiments were performed, the first consisting of the planting of seedlings tamboril in 24 kg pots. This was used a completely randomized design (CRD) in a split plot, and the plot formed by two different lighting environments: full sun and 50% reduction in brightness and subplots for ten hydrogel doses: 0.0; 2.0; 2.5; 3.0; 3.5; 4.0; 4.5; 5.0; 5,5 and 6,0 g L-1. The second was conducted in the field, a Planosol Haplic shanty town of Ibaretama (CE). The design was a randomized blocks (RBD) in factorial arrangement 2 x 4 with five repetitions. The treatments were four hydrogel doses (0.0, 4.0, 5.0 and 6.0 g L-1) and treatments with and without the addition of carnauba straw cover. It was determined at the end of the experiment 1 height, diameter, length and diameter of the root and shoot dry matter (SDM), root dry matter (RDM) and organic solutes levels. Throughout the field experiment was also evaluated by means of biometrics height and stem diameter of plants; the survival of seedlings; the total water potential and matric, and physico-chemical soil properties: density, porosity, aggregate stability and physical fractionation of organic matter. It was found that the application of hydrogel from 3.0 g L-1 increases the growth and tamboril dry matter, especially in shadowing condition. In the field it was concluded that the best development tamboril was achieved with the combination of carnauba straw and hydrogel, especially in the doses 4.0 and 5.0 g L-1 plant by, since they improve water retention in soil, the water supply and consequently the growth in height and diameter of tamboril grown in semi-arid degraded area.